Effects of 9/11 on Ali Akbar Siyal’s Poetry - Ahmad, Mazhar; Mukhtiar, Paghunda; Seemab, Sher Zaman (sourcecoder, 2023)
The incident of 9/11 had a profound effect on almost all the major languages of Pakistan, even the literature created in English in Pakistan and the English literature as a whole, as this incident is directly related to the politics, literature, history and geography of Pashtuns. Therefore, its reflection is very clear in Pashto language compared to other languages of Pakistan. The most important Pashto poet in relation to the impact of the Afghan war and specifically 9/11 is Ali Akbar Siyal. The main theme of Sial's Pashto poetry is hatred of war and terrorism and love of peace and tranquility. This article examines the impact of 9/11 on Ali Akbar Siyal's poetry.